2014
DOI: 10.1007/s11427-014-4694-2
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptors in energy homeostasis

Abstract: G-protein coupled receptors (GPCRs) compromise the largest membrane protein superfamily which play vital roles in physiological and pathophysiological processes including energy homeostasis. Moreover, they also represent the up-to-date most successful drug target. The gut hormone GPCRs, such as glucagon receptor and GLP-1 receptor, have been intensively studied for their roles in metabolism and respective drugs have developed for the treatment of metabolic diseases such as type 2 diabetes (T2D). Along with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…G protein-coupled receptors (GPRs) play pivotal roles in cell signaling to maintain energy homeostasis [21,22]. They are known to regulate various adipocyte functions, including FAO and thermogenesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…G protein-coupled receptors (GPRs) play pivotal roles in cell signaling to maintain energy homeostasis [21,22]. They are known to regulate various adipocyte functions, including FAO and thermogenesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence has suggested that GPR39 also displays ligand-independent constitutive activities. In population studies, associations have been found between polymorphic variants of GPR39 and the onset of pathologies, including cancer, cardiovascular diseases, nutrition, and energy homeostasis ( 13 16 ). In animal studies, GPR39 has been reported to participate in adipocyte metabolism ( 17 ) and regulate pancreatic islet function ( 18 ).…”
mentioning
confidence: 99%